PENINGKATAN KEMAMPUAN NUMERASI SISWA KELAS III SD MELALUI MODEL TEAM GAMES TOURNAMENT BERBANTUAN MEDIA SPINTAZ - Achmad Arif Budi Santoso; Herry Sanoto (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT This study aimed to improve the numeracy skills of third-grade students at SDN Karangtengah 01 through the implementation of the Team Games Tournament learning model assisted by Spintaz media. The study was motivated by students’ low numeracy skills in understanding mathematical concepts and solving contextual problems, indicating the need for a more interactive and enjoyable learning approach. The research employed a Classroom Action Research (CAR) method using the Kemmis and McTaggart model conducted in two cycles consisting of planning, action, observation, and reflection stages. The research subjects were third-grade students of SDN Karangtengah 01. Data were collected through observation, numeracy tests, and documentation. The results showed that the implementation of the Team Games Tournament model assisted by Spintaz media was able to improve students’ numeracy skills in each learning cycle. The improvement was indicated by the change in students’ learning outcomes from the poor category in the initial condition to the very good category after the actions were implemented. In addition, students became more active, enthusiastic, and engaged during the learning process, creating a more interactive and conducive classroom atmosphere. Therefore, the Team Games Tournament model assisted by Spintaz media is effective as an alternative learning approach to improve elementary school students’ numeracy skills. ABSTRAK Penelitian ini bertujuan untuk meningkatkan kemampuan numerasi siswa kelas III SDN Karangtengah 01 melalui penerapan model Team Games Tournament berbantuan media Spintaz. Penelitian dilatarbelakangi oleh rendahnya kemampuan numerasi siswa dalam memahami konsep matematika dan menyelesaikan soal kontekstual sehingga diperlukan pembelajaran yang lebih interaktif dan menyenangkan. Penelitian menggunakan metode Penelitian Tindakan Kelas (PTK) dengan model Kemmis dan McTaggart yang dilaksanakan dalam dua siklus melalui tahap perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Subjek penelitian terdiri atas siswa kelas III SDN Karangtengah 01. Data diperoleh melalui observasi, tes kemampuan numerasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa penerapan model Team Games Tournament berbantuan media Spintaz mampu meningkatkan kemampuan numerasi siswa pada setiap siklus pembelajaran. Peningkatan tersebut terlihat dari hasil belajar siswa yang mengalami perubahan dari kategori kurang baik pada kondisi awal menjadi kategori sangat baik setelah tindakan diberikan. Selain itu, siswa menjadi lebih aktif, antusias, dan terlibat selama proses pembelajaran berlangsung sehingga suasana belajar menjadi lebih interaktif dan kondusif. Dengan demikian, model Team Games Tournament berbantuan media Spintaz efektif digunakan sebagai alternatif pembelajaran untuk meningkatkan kemampuan numerasi siswa sekolah dasar.